Is Encapsulated Medullary Thyroid Carcinoma Associated With a Better Prognosis? A Case Series and a Review of the Literature - Contarino, Andrea; Dolci, Alessia; Maggioni, Marco; Porta, Francesca Maria; Lopez, Gianluca; Verga, Uberta; Elli, Francesca Marta; Iofrida, Elisabetta Francesca; Cantoni, Gianmaria; Mantovani, Giovanna; Arosio, Maura (Frontiers in Endocrinology, 2022)
Context: Medullary thyroid carcinoma (MTC) is a malignant neuroendocrine neoplasm that may spread to lymph nodes before the primary tumor is diagnosed; moreover, distant metastases are already present in about 10% of patients at diagnosis. Serum calcitonin (Ctn) usually reflects the spread of disease, thus orienting the extent of surgery and predicting the possibility of biochemical remission. Tumor size and vascular invasion are important prognostic factors, but little is known on the relationship between other histopathological features, such as the presence of a tumor capsule, and long term outcome of MTC. Purpose: To evaluate the prevalence of encapsulated tumors among MTCs and the association of tumor capsule with a favorable outcome after surgery. Methods: A retrospective observational single-center study was conducted together with a narrative review of the available literature. Results: Among 44 patients (27 female, 17 male; median age: 56 years) with MTC (6 hereditary, 37 sporadic) followed up at our center in the last four years (median follow-up: 29.2 months), seven (15.9%) showed an encapsulated tumor at histology and a clinical remission after surgery. None of them had nodal metastases and median preoperative Ctn (398 pg/mL, IQR 126.5–7336) did not differ significantly from that of the 14 patients (31.8%) with persistent disease after surgery (787 pg/mL, IQR 340.5–2905.5; p=0.633), although their tumor size was significantly higher (median 33 mm versus 16 mm respectively, p=0.036). Among patients with preoperative Ctn levels above 500 pg/mL (n=11), only two (18.2%) showed undetectable Ctn levels during follow-up, both having an encapsulated MTC (OR 0.000, p=0.02). Notably, they were two similar cases of large MTC (> 3 cm) with extensive hyalinization and calcification, associated with very high Ctn levels (> 13'500 and 1’100 pg/mL, respectively) but no nodal nor distant metastases, in complete remission after surgery although one of them carried the aggressive M918T somatic RET mutation. Conclusion: MTC rarely shows a tumor capsule, which seems to correlate with a better prognosis and absence of nodal metastases, regardless of RET or RAS mutational status. Among encapsulated MTCs (E-MTC), Ctn levels and tumor size are not predictive of persistence of disease after surgery.